Penggunaan Jaringan Sensor Nirkabel Untuk Pemantauan Suhu Mesin Tetas Telur Ayam - Dedy Nurahmadin; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Normally to check Hatching Machines are carried out by checking temperature stability in Hatching Machine’s rooms, one by one. This way can cause temperature instability to become a problem in incubation process of eggs. As a sequence, those eggs fail to hatch. Solution to this problem is a controlling and monitoring system of Hatching Machine by using Xbee Tansmitter and Xbee Receiver. Xbee Transmitter is connected to the Arduino Uno ATMega328 located in the Hatching Machine. DHT22 Sensor detects temperature Hatching Machine. Xbee Receiver connected to other Arduino Uno ATMega328 on the user’s place. The testing of temperature monitoring is performed for two hours by eading and sending temperatures every 10 minutes. Two LEDs, such as Red LED and Green LED, are used as indicator. If temperature in Hatching Machine is less than 37,8°C, so Red LED is On and Green LED is off when desired temperature can not be reached. If temperature is between 37,8°C upto 38,7°C, Green LED is On and Red LED is Off to indicate the needed temperature can be achieved. If temperature is over 38,7°C, so Red LED will be On and Green LED will be Off to indicate that the temperature is too high. Keywords: Egg, Temperature, Hatching Machine, Xbee Tansmitter and Receiver, Arduino Uno ATMega328